A inserção dos Palotinos na Quarta Colônia de Imigração Italiana - Silva, Algir Facco da (2020)
The present dissertation aims to investigate the insertion of Pallottine priests in The Fourth Colony of Italian Immigration - Quarta Colônia - in Rio Grande do Sul State, Brazil. Quarta Colônia was an important destination for Italian immigrants who, in the late 19th and early 20th centuries, headed for Brazil in search of better living conditions for their families. A group of Italian immigrants from Vale Veneto, a district of São João do Polêsine sent a representative to Europe with the objective of bringing priests to Brazil to accompany the life of the immigrants. In that occasion, they reached the Pia Sociedade das Missões, which accepted the invitation and sent priests to Brazil. Through bibliographical and documentary research, this study investigated the expansion of the evangelizing mission of the priests of the Pia Sociedade das Missões in the colonial nuclei of Quarta Colônia. When inserting themselves into the colonial nuclei, the Pallottines implemented their missionary project in line with the doctrine of the Roman Curia, which caused them to face resistance from some leaders, anticlerical groups, and liberal diocesan priests who did not approve of such mission. Despite facing resistance to their model of church, the Pallottines expanded their work in just a few years of mission, counting on the support of settlers faithful to their endeavor and the determinations of the Catholic Church. In 1896, they were invited by the diocesan bishop to take over the Santa Maria parish while facing opponents that did not want the Catholic Church to act in the political and social affairs of the city. The action of the priests in the administration of the parish managed to gather strength and support in order to expand their projects. The construction of the cathedral and the coming of educational congregations were decisive for the consolidation of the Pallottine mission in the city. In a tense social moment with several social constructions in motion, the Pallottines knew how to insert themselves into the political game in a decisive way and consolidate the Catholic Church as an active institution present politically and socially in the city.